1995
DOI: 10.1034/j.1399-3054.1995.950411.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled mycorrhizal initiation as a means to improve root development in somatic embryo plantlets of hybrid larch (Larix x eurolepis)

Abstract: Controlled mycorrhizal initiation as a means to improve root development in somatic embryo plantlets of hybrid larch {Larix X eurolepis) ¥. Piola, R. Rohr and P. von Aderkas Piola, F., Rohr, R. and von Aderkas, P. 1995. Controlled mycorrhizal initiation as a means to improve root development in somatic embryo plantlets of hybrid larch (Larix x eurolepis). -Physioi. Plant. 95: 575-580.This study represents the first report of in vitro myconhization of somatic embrj'O-derived plantlets. Effects of fungi on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…TI increase throughout the growth period and magnitude of increase in TI appeared to be high in treatment with industrial effluents in combination with VAM than with industrial effluents alone, this is in accordance with those obtained by Piola et al (1995) whom found that, development of root system was concomitantly accompanied by an enhancement of shoot growth due to effect of ectomycorrhizal fungi of hybrid larch.…”
Section: Growth Response and Yield Componentssupporting
confidence: 91%
“…TI increase throughout the growth period and magnitude of increase in TI appeared to be high in treatment with industrial effluents in combination with VAM than with industrial effluents alone, this is in accordance with those obtained by Piola et al (1995) whom found that, development of root system was concomitantly accompanied by an enhancement of shoot growth due to effect of ectomycorrhizal fungi of hybrid larch.…”
Section: Growth Response and Yield Componentssupporting
confidence: 91%
“…In fact, Suillus can kill seedlings under some conditions (Piola, Rohr & von Aderkas, 1995), which suggests that its biotrophic C demand might be too high in some cases. A more efficient C transfer for Suilloid fungi is also consistent with the specialist hypothesis of Cullings, Szaro & Bruns (1996).…”
Section: mentioning
confidence: 99%
“…This proves that suitable EM partners are crucial for the success of P. cembra afforestations and that they can be successfully introduced as inoculated seedlings. Swiss pine trees associated with suitable mycobionts have a higher vitality and produce more biomass than trees without [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%